2000
DOI: 10.1042/cs19990244
|View full text |Cite
|
Sign up to set email alerts
|

Increased left atrial thrombin generation in mitral stenosis is not reflected in arterial prothrombin fragment 1+2 levels

Abstract: A proportion of patients with mitral stenosis have increased left atrial thrombin generation, with elevated left atrial but normal peripheral venous levels of prothrombin fragment 1+2 (F1+2). Whether this pattern of left atrial and venous F1+2 levels is related to limited spillover of F1+2 from the left atrium into the systemic circulation, or to washout of increased left atrial F1+2 production into the arterial circulation with subsequent systemic clearance, is unclear. We examined the relationship between ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…First, patients in the study were on full-dose oral anticoagulation before and after the valvuloplasty procedure, and results may therefore have been influenced by the well-recognized effect of warfarin to reduce coagulation activity [23][24][25][26]. Secondly, the assumption of Yamamoto et al [7] that arterial F1j2 levels are representative of left atrial levels may not be correct, and has not been confirmed in a subsequent study [27].…”
Section: Discussionmentioning
confidence: 97%
“…First, patients in the study were on full-dose oral anticoagulation before and after the valvuloplasty procedure, and results may therefore have been influenced by the well-recognized effect of warfarin to reduce coagulation activity [23][24][25][26]. Secondly, the assumption of Yamamoto et al [7] that arterial F1j2 levels are representative of left atrial levels may not be correct, and has not been confirmed in a subsequent study [27].…”
Section: Discussionmentioning
confidence: 97%
“…Although they provide some data of levels of D-dimer, these alone are insufficient to be able to put the changes in F1j2 into a perspective of the wider field of coagulation and fibrinolysis. While Peverill et al [1] suggest that peripheral blood sampling may perhaps underestimate the degree of haemostatic activation in the left atrium, the process of thrombogenesis is unlikely to be confined to the left atrium itself in cardiovascular disease, and is likely to be a more generalized process. Indeed, levels of F1j2 can also be influenced by sampling methods [3].…”
mentioning
confidence: 91%
“…For example, the division of patients into ' normal ' and ' prolonged ' INR by Peverill et al [1] resulted in the latter group having only seven subjects. It is unclear why Peverill et al [1] chose an INR of 1n2 as the divider, when a better analysis would have been to compare groups above and below the median INR.…”
mentioning
confidence: 97%
See 2 more Smart Citations